1999
DOI: 10.1081/ss-100100787
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Textile Dye Plant Effluent by Nanofiltration Membrane

Abstract: The study was concerned primarily with characterization of the NF45 membrane. Its pure water permeability, the mass transfer coefficient of NaCl, and the mean radius of the membrane pores were determined. Experiments run with five pure dye solutions and an industrial dye pulp solution confirmed the potential of nanofiltration membrane separation for the treatment of textile dye plant effluent. The effects of such significant parameters as initial solution concentration, transmembrane pressure, and type of dye … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
0
6

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(54 citation statements)
references
References 6 publications
(6 reference statements)
0
48
0
6
Order By: Relevance
“…Therefore, textile dyeing wastewater treatment has received more attention in the last few decades [2][3][4]. Different techniques are used for removing hydrophobic dyes, such as electron oxidation, ozonation, electro-kinetic coagulation ion, membrane filtration and microbial degradation [5][6][7][8][9][10]. These techniques have some advantages and disadvantages over the other techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, textile dyeing wastewater treatment has received more attention in the last few decades [2][3][4]. Different techniques are used for removing hydrophobic dyes, such as electron oxidation, ozonation, electro-kinetic coagulation ion, membrane filtration and microbial degradation [5][6][7][8][9][10]. These techniques have some advantages and disadvantages over the other techniques.…”
Section: Introductionmentioning
confidence: 99%
“…13 Separation factors for different reactive dyes of greater than 98.5% have been achieved using nanofiltration membranes. 14 The most important parameters in economic terms for the direct reuse of dye bath wastewaters are the flux and the recovery rate of sodium chloride. Consequently, current studies have been orientated to maximise these parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Analyzed from the structure of adsorbent and contaminate molecule, it is known that the adsorption of these charged dye groups onto the adsorbent surface is primarily influenced by the surface charge which is in turn influenced by the solution pH [18]. Figure 7 shows the effects of initial MB concentrations (5,10,20,30,40, and 50 mg/L) on BG-La-1∼5 and undoped mesoporous bioactive glasses (BG-1∼5). It can be easily observed that the removal rates of BG-La-1∼5 are higher than BG-1∼5, and the removal rate decreased with the increase of initial MB concentrations.…”
Section: Effect Of Initial Solution Phmentioning
confidence: 99%
“…In particular, organic pollutants [1] that include dyes [2,3] and agricultural wastes [4] are released into the environment and can be transported over long distances in the atmosphere, water, and land. Therefore, in order to purify water, many technology have been developing and developed, such as membrane filtration technology [5], coagulation and flocculation technology [6], electrochemical oxidation technology [7], adsorption technology [8][9][10], biological treatment technology [6,11], and advanced oxidation process (AOP) [12]. However, some of the techniques shown in the effect are not ideal in practice.…”
Section: Introductionmentioning
confidence: 99%